Mempercepat Keputusan Pembelian Melalui Peran Mediasi Citra Merek di Fore Coffee Kelapa Gading - Eva Hubaydillah; Parlagutan Silitonga (Human Capital Development, 2022)
This study aims to determine and prove the effect of product quality and price perceptions on purchasing decisions through brands at Fore Coffee Kelapa Gading. The population in this study were customers of Fore Coffee Kelapa Gading. The sampling technique used an accidental sampling of as many as 132 respondents. The data collection method used a questionnaire distributed to respondents. Meanwhile, hypothesis testing includes path analysis with the help of SmartPLS 3.0. The results of this study that product quality and price perception directly have a positive and significant effect on brand image, price perception and brand image have a positive and significant effect on purchasing decisions, and there is significant indirect effect of product quality on purchasing decisions through brand image. However, product quality has no significant effect on purchasing decisions. The result of the coefficient of determination on the brand image is 61.9% and the purchase decision is 70.9%.